Application of dental pulp stem cells for bone regeneration - Liu, Ye (Frontiers in Medicine, 2024)
Bone defects resulting from severe trauma, tumors, inflammation, and other factors are increasingly prevalent. Stem cell-based therapies have emerged as a promising alternative. Dental pulp stem cells (DPSCs), sourced from dental pulp, have garnered significant attention owing to their ready accessibility and minimal collection-associated risks. Ongoing investigations into DPSCs have revealed their potential to undergo osteogenic differentiation and their capacity to secrete a diverse array of ontogenetic components, such as extracellular vesicles and cell lysates. This comprehensive review article aims to provide an in-depth analysis of DPSCs and their secretory components, emphasizing extraction techniques and utilization while elucidating the intricate mechanisms governing bone regeneration. Furthermore, we explore the merits and demerits of cell and cell-free therapeutic modalities, as well as discuss the potential prospects, opportunities, and inherent challenges associated with DPSC therapy and cell-free therapies in the context of bone regeneration.